Study Of Challenges For Higher Educational Institutions During Covid-19 Pandemic - Thakur, Jagvinder (Gyan Management Journal, 2020)
COVID-19 is a recently discovered strain of coronavirus family that have never seen in human beings before. Due to its contagious nature or human to human transfer ability, it is ouicially declared as the worldwide pandemic by World Health Organization. During this pandemic time, it is necessary to shut down all the human activities to contain the spread and educational institutions are no exception. In this article, I will highlight some of the key challenges that are being faced by higher educational institutions while containment of the spread of this virus without disrupting the studies of its students.